Optimization of Web-Based Service Management System Using Time and Material Pricing for Tool Maintenance - Muhammad Khusnud Dhonni; Danang Mahendra; Noor Azizah (Komunitas Dosen Indonesia, 2025)
This study develops a web-based Service Management Information System tailored for small-scale tool maintenance businesses that traditionally lack integrated management solutions. These micro enterprises commonly encounter operational inefficiencies such as poor workflow management, inaccurate cost estimation, and manual transaction recording, which hinder service quality and diminish customer trust. The proposed system addresses these challenges by automating critical service functions, including customer queue management, technician diagnostics, spare parts tracking, and invoice generation, thereby improving operational efficiency and transparency. The development process followed the Waterfall model within the Software Development Life Cycle (SDLC), providing a structured framework covering requirement analysis, system design, implementation, testing, and maintenance phases. A key feature of the system is the integration of the Time and Material Pricing (T&M) method, enabling dynamic cost calculation based on actual labor hours and material usage. This method ensures fair and transparent pricing, which is vital for sustaining customer confidence in environments with variable service demands. Functional validation through Black Box Testing confirmed that the system’s core modules met all specified requirements without significant errors. Furthermore, a user satisfaction survey involving 30 respondents indicated substantial improvements in cost transparency, service speed, and ease of status tracking. Overall, the system markedly enhances both operational performance and customer experience in small tool maintenance workshops. The findings suggest that this web-based solution supports digital transformation in a traditionally manual sector, promoting competitiveness and sustainability for micro enterprises. Future enhancements include mobile application development and integration of digital payment systems to further optimize service delivery.